Ação docente em ciências naturais na Educação de Jovens e Adultos (EJA): um olhar histórico-crítico e histórico-cultural - SIMIRIO, Lucas Vilas Boas (2020)
The teaching action in Youth and Adult Education (EJA) runs through a context of profound political and historical-social contradiction, especially in the teaching-learning of Sciences, which has lacked less expository and more critical-emancipatory practices for social transformation of their subjects. In view of this problem, the present research, linked to the UNOESTE Postgraduate Program in Education (PPGE), tried to analyze, from the epistemological matrix of historical-dialectical materialism, which theoretical-methodological and pedagogical actions are taken by teachers of Physical and Biological Sciences of the final grades of Elementary Education of EJA and its articulations with the formation of the student. In this way, a qualitative study was developed, theoretically structured from the dialectical approach proposed by Historical-Critical Pedagogy and Vygotsky's Historical-Cultural Psychology. In view of this, the typology of the Case Study was adopted, which consisted of a singular understanding of the didactic assumptions of the teaching activity of three (03) science teachers in the exercise of their function in the EJA, and the investigation of the learning of 12 students in the face of their activity professionals, in two municipal schools in the interior of São Paulo, between the final grades of Elementary Education. To this end, four procedures were used for data collection: a questionnaire applied to teachers with closed questions about their training and teaching actions; a questionnaire with open and closed questions to students to verify science learning; logbook through observations of teachers' classes; and, a semi-structured interview with the teachers for a deeper understanding of their praxis in this modality. Finally, the information apprehended was discussed based on Bardin's Content Analysis (1977), according to the elaboration of four axes of analysis, among them: “Science teaching at EJA”; “EJA students and the science teaching-learning process”; "The Youth and Adult Education (EJA) modality" and "The teaching and learning practice in Science at EJA". Thus, it was concluded that the practice of these teachers is still characterized by the reproduction of traditional and technical theories; and, through the use of transmissive methodologies, without articulation with historical-social issues. Students have a purely biological and utilitarian conception of science. Teachers have poor training to work in EJA. The learning of these students is still out of context and without social commitment. The most common teaching trend is based on everyday life, with an emphasis on conceptual content. The evaluations are, in general, selective and uniform. There was also a need to overcome the mechanistic paradigm of scientific education in EJA, above all, by adopting training and teaching based on PHC and Historical-Cultural Psychology; since both theories value the humanization of the student subject, his social transformation and full democratic experience in the light of the dialectic.